Complementation Test between Alkaline Phosphatase Regulatory Mutations phoB and phoRc in ESCHERICHIA COLI - Pratt, Charles (1977)
A phoRc and a phoB mutation belong to the same complementation group suggesting that there is a single positive control gene for alkaline phosphatase synthesis.